MAGNETIC PHASE TRANSITIONS OF T-PHASE Gd2CuO4 SINGLE CRYSTAL - I. M. Sutjahja; M. Diantoro; A. A. Nugroho; A. Menovsky; M. O. Tjia (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2002)
MAGNETIC PHASE TRANSITIONS OF T-PHASE Gd2CuO4 SINGLE CRYSTAL. The magnetic properties of T‘-phase Gd2CuO4 Single crystal grown by the Traveling Solvent Floating Zone (TSFZ) method have been investigated by means of ac-magnetic susceptibility and dc-magnetization measurements. The result of these studies revealed an anomaly in the temperature dependent magnetization at temperature of T = 6.5, 290 and 20 K, associated respectively with the long-range antiferromagnetic ordering of the Gd and Cu ions and Cu- spin reorientation transitions. The complex magnetic structure of this compound shown by the weak ferromagnetic behavior below the copper ordering temperature (TN(Cu) = 290 K) is induced by an effective ﬁeld due to exchange interactions between the ordered copper moments and the rare-earth ions. These results, together with the previous neutron diffraction measurement, establishes the existence of ferromagnetic Gd layers in the ab-plane which are stacked antiferromagnetically along c-direction, indicating a quasi—two dimensional antiferromagnetic nature of Gd2CuO4.